Immuno-modulatory and anti-inflammatory effects of Thymus vulgaris, Zataria multiflora, and Portulaca oleracea and their constituents - Mohammad Reza Khazdair; Zahra Gholamnezhad; Ramin Rezaee; Mohammad Hossein Boskabady (Elsevier, 2021)
Medicinal herbs are widely used in the both traditional and modern medicines. Thymus vulgaris (T. vulgaris), Zataria multiflora (Z. multiflora), and Portulaca oleracea (P. oleracea) have been traditionally known as medicinal herbs. In this article, immune-modulatory effects of T.s vulgaris, Z. multiflora, and P. oleracea and their constituents, are reviewed. To this end, relevant articles, books, and conference papers published in English, until the end of September 2020, were retrieved from Web of Science, PubMed, Scopus and Google Scholar databases. Based on the literature, T. vulgaris and thymol reduced IL-6, IL- 1β and tumor necrosis factor α (TNFα) at both gene and proteins levels. Z. multiflora and carvacrol increased serum levels of IFN-γ but reduced IL-4 levels. P. oleracea and quercetin decreased T helper 2 (Th2)/Th1 and Th2/ regulatory T cells (Tregs) ratios by inducing IL-10 but suppression of IL-4. Together, these medicinal plants might be considered for the treatment of conditions associated with immune-dysregulation such as asthma and cancer.